4-SÜBSTİTÜE ALKOKSİ GRUBU İÇEREN YENİ TİP FTALOSİYANİNLERİN SENTEZİ VE BAZI ÖZELLİKLERİNİN İNCELENMESİ - KÖKÇİN, ALİYE AYLİN (Fırat Üniveristesi, 2012)
Bu çalışmada, yeni tetrahidrofurfuril alkol sübstitüe metalsiz ve metalli ftalosiyaninlerin sentezleri gerçekleştirildi.Deneysel çalışmanın birinci adımında tetrahidrofurfuril alkol grubu içeren ftalonitril türevi elde edildi. Bu tetrahidrofurfuril alkol ile 4-nitroftalonitril'in baz katalizli nükleofilik aromatik nitro grubu yer değiştirme reaksiyonu ile yapıldı. Bu reaksiyon kuru DMF içinde baz olarak susuz K2CO3 kullanılarak 75-80 0C'de iyi bir verimle gerçekleştirildi.Deneysel çalışmanın ikinci adımında ftalosiyanin bileşiklerinin sentezleri yapıldı.Metallo ftalosiyaninler uygun ftalonitril türevi ve metal tuzlarının (Co(II), Ni(II), Zn(II), Cu(II) asetatları) çözücüsüz ortamda ısıtılmasıyla elde edildi.Metalsiz ftalosiyanin (H2Pc), ftalonitril bileşiği ile DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) karışımının çözücüsüz ortamda ısıtılmasıyla sentezlendi.Ftalosiyanin bileşiklerinin yapıları UV-Visible, IR, 1H-NMR gibi farklı spektroskopik teknikler kullanılarak aydınlatıldı.Anahtar Kelimeler: Ftalosiyanin, Metalli ftalosiyanin, Sentez

In this work, the synthesis of new tetrahydrofurfuryl alcohol substituted metallo- phthalocyanines were described, heating without solvent methods.The first step in the synthetic procedure was to obtain phthalonitrile derivative containing tetrahidrofurfuryl alcohol group. This was accomplished by a base catalyzed nucleophilic aromatic nitro displacement of 4-nitrophthalonitrile with tetrahydroforfuryl alcohol. This reaction was carried out at 75-80 oC in DMF with K2CO3 as the base with good yield.The second step in the synthetic procedure was to obtain phthalocyanine compounds.The metallophthalocyanines were prepared from the corresponding phthalonitrile derivative and the metal salts (Co(II), Ni(II), Zn(II), Cu(II) acetates) by heating without solvent.The metal-free phthalocyanine (H2Pc) was also synthesized by heating a mixture of the phthalonitrile compound with DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) in the absence of solvent.Pcs were characterized using different spectroscopic techniques (FT-IR, UV?Vis, and 1H-NMR).Key Words: Phthalocyanine, Metal phthalocyanines, Synthesis
The synthesis and some properties of a novel type of phthalocycanine containing 4- substituted alkoxy group
Keywords: Kimya